Non-radioactive automated sequencing of oligonucleotides by chemical degradation. - Ansorge, W (1988)
A non-radioactive sequencing of fluorescently labelled oligonucleotides by solid-phase chemical degradation is described. Although non-radioactive methods have been reported for the dideoxy chain termination technique, such a method has not yet been developed for the chemical degradation sequencing of DNA fragments. A 21-mer fluorescein labelled M13 sequencing primer was sequenced in an on-line automated system in about 30 minutes. The fluorescent dye and its bond to the oligonucleotide were stable during the chemical reactions used for the base specific degradations. As the sequence is determined on-line during electrophoresis, reloading and running 10 fragments simultaneously allows us to use one gel for sequencing of about 50 different oligonucleotides.